Correlation Between Lecturer’s TPACK Mastery and Students’ Critical Thinking Skills - Windayani, Ni Luh Ika; Kristiawan, Muhammad; Putra, Ida Bagus Komang Sindu (The Indonesian Institute of Science and Technology Research, 2025)
The study's objectives are to investigate the relationship between lecturer mastery of Technology Pedagogical Content Knowledge (TPACK) and critical thinking skill development of students in the early childhood teacher education program. Based on a quantitative approach, this study shows a high correlation, which indicates a significant correlation between lecturers’ TPACK mastery and students’ higher-order critical thinking skills. A regression analysis also found that mastery of TPACK has a significant influence on critical way of thinking, which suggests that teachers who develop technology integration practices will assist in developing critical thinking among students. This study adds to the educational literature that TPACK is crucial for promoting this important 21st-century student skill. They realise that the amount of their sample reached the limit of the findings and recommend more compact research involving larger and more diverse samples to replicate these findings in a wider range of educational contexts. These findings reinforce the position of TPACK as a foundational element in promoting critical thinking in teacher education.